2018
DOI: 10.1002/ece3.4159
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of female reproductive resource allocation depends on the presence or absence of prior environmental sex determination in Ceratopteris richardii

Abstract: Resource allocation plasticity enables individuals to alter patterns of nutrient use between reproductive and vegetative output to better fit their current environment. In sexually labile plant species, abiotic environmental factors can influence expression of dimorphic gender, resulting in environmental sex determination (ESD), which potentially reduces the need for plasticity of resource allocation by preemptively matching an individual’s future nutrient demands to resource availability in its location. Cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…megalanthum considered the dual needs of belowground root space expansion and aboveground leaves to obtain light energy resources, and promoted the simultaneous growth of aboveground and belowground parts ( Bai et al., 2020 ). In addition, the response of plants to the potential limitation of essential nutrients makes them reallocate resources based on the trade-off of important organ resource demand ( Goodnoe and Hill, 2018 ). When the content of nitrogen and phosphorus in the soil was low (potassium addition treatment), the Lilium concolor var.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…megalanthum considered the dual needs of belowground root space expansion and aboveground leaves to obtain light energy resources, and promoted the simultaneous growth of aboveground and belowground parts ( Bai et al., 2020 ). In addition, the response of plants to the potential limitation of essential nutrients makes them reallocate resources based on the trade-off of important organ resource demand ( Goodnoe and Hill, 2018 ). When the content of nitrogen and phosphorus in the soil was low (potassium addition treatment), the Lilium concolor var.…”
Section: Discussionmentioning
confidence: 99%
“…Variability of sex expression is a key survival strategy in the life history of a few plants. Studies have shown that the reproductive success of sessile plants depends heavily on their ability to respond to environmental changes ( Goodnoe and Hill, 2018 ). If plants can choose more effective sexual functions according to environmental changes and can change sex expression with environmental changes, then this sexual strategy is the most adaptive ( Zhang et al., 2014 ; Niu et al., 2017 ; Blake-Mahmud and Struwe, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation